2002
DOI: 10.1111/1469-7610.00056
|View full text |Cite
|
Sign up to set email alerts
|

Conversational behaviour of children with Asperger syndrome and conduct disorder

Abstract: The results showed that in these contexts children with Asperger syndrome were no more verbose as a group than controls, though they showed a tendency to talk more in more emotion-based conversations. Children with Asperger syndrome, as a group, performed similarly to control subjects in ability to respond to questions and comments. However, they were more likely to show responses which were problematic in both types of conversation. In addition, individuals with Asperger syndrome showed more problems in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 27 publications
6
91
2
5
Order By: Relevance
“…This finding is against the previous case studies with descriptions of AS participants typically engaging in long, egocentric monologues [see e.g., 12,46]. However, the AS group may contain a small number of individuals with extreme verbosity, which-albeit not being a reliable characteristic of the AS group as a whole-may color our impressions of it [2]. Another possibility is that-given our instructions for the raters to consider dominance as a holistic, and not merely as a verbal phenomenon-our measure of dominance was more about nonverbal displays of dominance, thus tapping into a different aspect of behavior than the one in the studies cited above.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…This finding is against the previous case studies with descriptions of AS participants typically engaging in long, egocentric monologues [see e.g., 12,46]. However, the AS group may contain a small number of individuals with extreme verbosity, which-albeit not being a reliable characteristic of the AS group as a whole-may color our impressions of it [2]. Another possibility is that-given our instructions for the raters to consider dominance as a holistic, and not merely as a verbal phenomenon-our measure of dominance was more about nonverbal displays of dominance, thus tapping into a different aspect of behavior than the one in the studies cited above.…”
Section: Discussioncontrasting
confidence: 75%
“…Our results are twofold: [1] we compared the patterns of interpersonal behavior displayed in male dyads where one participant has Asperger's syndrome (AS) to those displayed in male dyads with two neurotypical (NT) participants and [2] examined the experiential consequences of these patterns for the participants in the two different types of dyads (AS dyads, NT dyads). Next, we will discuss these two types of results in two separate sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many interventions to improve symptoms of ASD have focused on children [10][11][12] , there is evidence that these difficulties persist with age [13][14][15][16]. As adults, individuals with autism are faced with an even greater variety of social interactions and complexities, as well as the expectation of greater independence in navigating them.…”
Section: Introductionmentioning
confidence: 99%
“…Volden, Mulcahy, and Holdgrafer (1997) found that children with autism produced a greater number of unusual utterance features and interrupted the flow of the interaction with more inappropriate statements, in comparison to age-matched normally developing controls. Finally, Adams and her colleagues (Adams, Green, Gilchrist, & Cox, 2002) found that adolescents with autism spectrum disorder provided more tangential and inadequate responses in conversation with an examiner, especially when discussing personal events.…”
mentioning
confidence: 99%